Multiparametric ultrasound (MPUS) evaluation of the testes of normozoospermic dogs – a pilot study - Aires, Luiz Paulo Nogueira [UNESP]; Gasser, Beatriz; Del'Aguila-Silva, Priscila [UNESP]; Gonçalves, Joedson Dantas [UNESP]; Uscategui, Ricardo Andres Ramirez; Spada, Stefano; De Felice, Daniela; Russo, Marco; Lima, Bruna Bressianini; Gimenes, Lindsay Unno [UNESP]; Feliciano, Marcus Antônio Rossi [UNESP] (Nature Publishing Group, 2025)
Ultrasound is an important tool in small animal andrology for assessing the integrity of the testes. This study explores ultrasound’s role in assessing the canine testes and understanding the correlation of sonographic parameters to sperm quality. It investigates B-mode and Doppler ultrasound techniques alongside advanced methods like Shear-wave Elastography (SWE) and Contrast-enhanced ultrasound (CEUS). The aim was to standardize a multiparametric ultrasound (MPUS) evaluation protocol using these techniques in normozoospermic dogs. Eight healthy male dogs were assessed. B-mode assessed testicular morphology, while Doppler evaluated testicular artery waveform morphology and velocimetric parameters. SWE measured testicular stiffness, and CEUS assessed testicular perfusion. Seminal parameters were also analyzed. Results revealed normal B-mode sonographic findings and some correlations between Doppler parameters and sperm quality. SWE demonstrated consistent testicular stiffness regardless of the depth of evaluation, with correlations of the stiffness of the head of the epididymis to the ejaculate volume. CEUS identified blood flow differences between testes and some perfusion parameters correlated with sperm features. This comprehensive ultrasound assessment provides valuable insights into canine reproductive health, providing basis for further studies on dogs with abnormal sperm quality and with different fertility statuses.
Avaliação ultrassonográfica multiparamétrica dos testículos de cães normozoospérmicos - estudo piloto
Keywords: Doppler, Ultrassonografia; Meios de contraste (Diagnóstico por Imagem); Veterinary andrology